2014
DOI: 10.1001/jama.2014.3200
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Conservative Management or Intervention for Unruptured Brain Arteriovenous Malformations

Abstract: Among patients aged 16 years or older diagnosed as having unruptured bAVM, use of conservative management compared with intervention was associated with better clinical outcomes for up to 12 years. Longer follow-up is required to understand whether this association persists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(56 citation statements)
references
References 30 publications
1
51
1
3
Order By: Relevance
“…(2012) were able to show that early surgical resection was associated with better overall survival than initial biopsy and watchful waiting. Another population‐based study from Scotland on patients with unruptured brain arteriovenous malformations showed that conservative management was associated with better clinical outcomes than treatment interventions (Salman et al., 2014). Using prospectively collected data from the Norwegian Registry for Spine Surgery, Nerland and coauthors were able to demonstrate that the effectiveness of laminectomy and microdecompression was equivalent in the management of lumbar spinal stenosis (Nerland et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012) were able to show that early surgical resection was associated with better overall survival than initial biopsy and watchful waiting. Another population‐based study from Scotland on patients with unruptured brain arteriovenous malformations showed that conservative management was associated with better clinical outcomes than treatment interventions (Salman et al., 2014). Using prospectively collected data from the Norwegian Registry for Spine Surgery, Nerland and coauthors were able to demonstrate that the effectiveness of laminectomy and microdecompression was equivalent in the management of lumbar spinal stenosis (Nerland et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Data from these registries can be used in epidemiological studies as they are easily obtained, include high number of patients, and provide both high external validity and statistical power (Jakola et al., 2012; Nerland et al., 2015; Salman et al., 2014; Sorensen, 1997). Administrative health registries need to have accurate diagnoses and sufficient coverage in the population they serve in order to be useful in research.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,19 The notion that patients with unruptured AVMs can be harmed by intervention more than conservative management was suggested by the early analysis of ARUBA, as well as by the prospective, observational AVM cohort study from the Scottish Audit of Intracranial Vascular Malformations. 12,20 ARUBA has been appropriately scrutinized for its numerous methodological weaknesses. 13 By analyzing a multicenter cohort of ARUBA-eligible patients treated with radiosurgery alone, we endeavor to address some of these weaknesses.…”
Section: February 2016mentioning
confidence: 99%
“…[1][2][3] In patients with ruptured AVMs, the annual risk of rebleeding has been estimated to be between 3.7% and 7.5%. [4][5][6][7][8][9][10] Radical treatment, including surgical excision, radiosurgery, endovascular treatment, and combinations of these procedures, is considered when the risks associated to a therapeutic intervention are estimated to be lower than the accumulated risks of the outcomes of AVM-related cerebral hemorrhage. 2 In contrast, for patients with an unruptured AVM, therapeutic intervention remains uncertain because the expected risk for cerebral hemorrhage with the natural history of AVMs largely depends on the characteristics of the patients selected for observation and on the definition of the starting point of observation.…”
mentioning
confidence: 99%
“…The annual bleeding risk of observed AVMs has been reported to be relatively low, ranging between 1.3% and 4.0%, even when the period of observation has been limited to the time from diagnosis to the last follow-up. [4][5][6][7][8][9][10] Therefore, there is a significant clinical controversy around recommendation of invasive interventions of AVMs, considering their relatively benign natural course.…”
mentioning
confidence: 99%